ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP STRUKTUR MODAL PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2009-2011) - Mufid Pinto Nugroho; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2013)
The aim of this research is to analyze the effect of corporate governance to corporate capital structure. Capital is very important in building and ensuring the continuity of the company. The additional capital will be required if the company is doing expantion. Accomplishment of the company's capital can raises agency problems so it’s necessary to make corporate governance. Corporate governance used in this research are boards size, outside directors, institutional ownerships, managerial ownerships and remunerations.This research used annual report of manufacturing companies listed in Indonesia Stock Exchange (IDX) 2009-2011. The sampling method in this research is purposive sampling, the amount of samples are 198 samples. This research used multiple regression analysis data and hypothesis.Result’s show that the outside directors has significant and negative effect to the capital structure and institutional ownerships are positively and significant affected to capital structure. While the other variables such as the board size, managerial ownerships and remunerations are not significantly affected to capital structure. This research also find that the control variables which are profitability, liquidity, asset tangibility have significant and negative effect to capital structure and for the firm size do not have significant effect.